Концепції розвитку культури - Бочарова, М. І. (ХНУРЕ, 2023)
The development of culture took place under rather difficult conditions and is connected with the historical development of society. At the same time, cultural knowledge is quite specific and affects many directions of the development of society. However, without cultural knowledge, one cannot talk about a civilized person, society, and the unimaginable progress of the future of mankind. Culture increases the quality of life, concentrates the social experience of many generations, and accumulates knowledge about the world. Culture is an important part of the life of every person and society as a whole.